Prospects for the exploration of gold deposits in the Golovanevsk suture zone of the Ukrainian shield - Pavlyuk, V.N.; Entin, V.A.; Gintov, O.B.; Guskov, S.I. (Geofizicheskiy Zhurnal, 2019)
Prospects for the search for gold deposits within the limits of the Lypovenky-Sukhiy Tashlyk area of the Golovanivsk suture zone (GSZ) of the Ukrainian Shield (USh) have been considered, where in the 80―90s of the last century North Capitanian gold mineralization with indicative reserves of 27 tons of Au was discovered and drilling of more than 3000 wells with hydrotransportation of the core (CHC) in the crust of weathering of the Precambrian basement revealed signs of about 30 new massifs of rocks of hyperbasite composition. Drilling was directed at the search for deposits of silicate nickel, so was not paid attention enough to the presence of hypergene gold in more than half wells was not given enough. In this paper, the authors turned to this question, because the search for gold deposits within the USh is now in time. The work is based on the analysis and generalization of geological, archival laboratory data and results of detailed geophysical works at a scale of 1:10 000. The conclusion of previous studies confirmed that one of the important search criteria for gold mineralization is the presence of metasomatic, dynamometamorphic and skarn transformations in endocontact zones of massifs of basites and ultra-basites, as well as in the zones of intersection of such massifs with faults. Metasomatites and skarns have the largest weathering crust among other types of rocks, and the stem capacity of abnormal gold-bearing intervals may exceed 10 m. The largest number of ”gold-bearing” wells has just been recorded in the skarns, and the average content of Au in the weathering crusts of the main types of rocks in the research area is the largest one in the skarns and ultra-basites. The analysis of the maps of abnormal magnetic and gravitational fields allowed, in addition to the known here zones of faults in the northwest, to distinguish two meridional zones of shearing that coincide with the separate Lypovenky and Sukhiy Tashlyk areas of development of gold mineralization. Both areas of shearings consist of meridional and latitudinal echelon shears, many of which are bordered with bodies of basites and hyperbasites and accompanied by chains of gold anomalies. Shearing zones belong to the Subot-Moshorino phase of faulting (1.8―1.73 billion years ago), with which the active processes of ore formation of rare and noble metals are connected within the USh. Recommendations for further geological and geophysical investigations within the limits of Lypovenky―Sukhiy Tashlyk area of the GSZ have been given.